The effect of the application of cold on hematoma, ecchymosis, and pain at the catheter site in patients undergoing percutaneous coronary intervention - Yeter Kurt; Mağfiret Kaşıkçı (Elsevier, 2019)
Objective: This study was conducted to determine the effect of the application of cold on hematoma, ecchymosis, and pain in patients undergoing percutaneous coronary intervention. Methods: It is a quasi-experimental study with a control group. A total of 200 patients (100 in the control group and 100 in the experimental group) were included in the research. In the experimental group, a cold pack was applied to the bottom of the sandbag for the first 15 min after withdrawing the femoral arterial catheter. Both groups were assessed and followed up at the first 15th minute and 4th, 48th and 72 nd h. Results: After the femoral arterial catheter was withdrawn, ecchymosis and hematoma were smaller and pain was less in the experimental group at the catheter entry site compared to the control group, and the difference was statistically significant (P < 0.01). Conclusion: It was determined that the application of cold reduced the formation of hematomas, ecchymoses and pain in patients after the withdrawal of the femoral arterial catheter. Keywords: Cold compress, Ecchymosis, Hematoma, Nursing care, Pain, Percutaneous coronary intervention